Identidades híbridas: processos de subjetivação através da fragmentação e (des)montagem digital - Siminovich, Denis (2009)
This research proposes a reflection and analysis on issues related to the hybridization procedures of contemporary art, with the thread, my artistic process. Develop a visual output based on digital photography on hybrid identities in self-portraits and portraits. This study involves the examination of the artistic device of procedures resulting from crosses of photography and painting in the use of digital technologies, through processes of Photomontage. The procedures cover the treatment of remains of digital photographs 3x4cm coupled with other appropriate images and copyright. The thrust of the analysis are impregnation and displacement of original images, with other senses. It s about a Poiétic study involving the analysis of the personal work based on the operations of fragmentation and (un)mounting digital and conceptual research and that seeks a theoretical context in relation to production in contemporary art. The text provides a built in search parameters and academics whose artistic proposition follows the path of other studies that also dealt with the artists to investigate or address the issue of identity in art and in real life.